AUTOCLAVE-ASSISTED DEACETYLATION: A RAPID METHOD TO RECYCLING CIGARETTE BUTTS TO CELLULOSE - Putri Amanda; Anisyah Putri; Nanang Masruchin; Wida Banar Kusumaningrum; Riska Surya Ningrum; Ismadi Ismadi (Jurnal Sains Materi Indonesia, 2020)
AUTOCLAVE-ASSISTED DEACETYLATION: A RAPID METHOD TO RECYCLINGCIGARETTE BUTTS INTO CELLULOSE. Cellulose acetate (CA)-based materials, like cigarette butts (CBs), become one of the most com-mon types of litter in the world. The toxic substances that are contained make this waste carry a hazardous risk for the environment and living organisms. Herein we report a rapid method for recycling cigarettes butts into more environmen-tally material. Cellulose was fabricated by deacetylation of cigarette butts with NaOH solution at various times 15, 30, 45, and 60 minutes in autoclave. Cellulose was optimized by a degree of deacetylation (DD%) and was further charac-terized by FTIR, SEM, TGA, and DSC analysis. The DD% and FTIR results confirmed the complete conversion of cellu-lose acetate from cigarette butts to cellulose within 15 minutes. Cellulose morphology under SEM showed the surface became rougher and textured after autoclave treatment. The results of autoclave-assisted deacetylation are comparable with the conventional deacetylation. Our rapid method offers substantially reduced deacetylation from 24 hours to just 15 minutes. This study has shown that the new and straightforward method for deacetylation cellulose acetate and it is potential as an alternative method for recycling cigarette butts waste in the future.